Management Information System and Organisational Performance of Service Industry in Nigeria - Lawal, Raheem; Afolayan, Michael Ayorinde (Acta Universitatis Danubius. Œconomica, 2023)
The implementation of a management information system necessitated rearranging workplaces to better accommodate regional networks and division integrated systems. The goal of this study is to collect hard data on how MIS affects business outcomes. Survey method was employed. Fifty (50) participants were randomly picked from the pool using simple random selection methods. Pearson Product Moment Correlation (r) was used to test all the hypotheses. The Findings from hypotheses showed that all the p- value (significant) level being 0.01 are less than 0.05, (p=0.01<0.05), therefore all the hypotheses were rejected. The study therefore concluded that MIS improves employee performance and their analytical skills. The study then recommended among others that managers of service organisation should ensure proper and adequate security of computer to prevent unauthorized access to the system.